Studies on Some Promising Fodder Plants of Hassan District, Karnataka - Kumar, G. M. Prashanth; Shiddamallayya, N. (Indian Forester, 2018)
The present communication describes 87 fodder plant species belonging to 83 genera and 34 families which are the sources of fodder. The local name of the plant, period of availability, occurrence, part used and other details with pertinent comments are enumerated. Family Poaceae was represented by 26 species, followed by Fabaceae and Moraceae (6 species each). The most preferred fodder plants as perceived by informants revealed that Echinochloa crusgalli was the most important fodder species.